Analisis Strategi Pemasaran 4P pada Produk Nasi Cokot Ceria - Sevia Nur Kamila; Muhammad Anas (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
I In the modern era, digital marketing has grown rapidly and has become a major tool in marketing strategies. Social media is not only a communication platform but also an effective means to increase branding and engagement with customers. This research focuses on CV. Arbain Jaya Mandiri, a micro business in Solo, produces honey, herbal products, and cosmetics. Before using digital marketing strategies, companies still had limitations in significantly increasing brand awareness. This study aims to identify effective digital marketing strategies through social media, analyze appropriate social media platforms to improve branding and measure the success of digital marketing strategies. The method used in this study is a qualitative method with Participatory Action Research. Participatory Action Research is research that involves relevant parties (stakeholders) directly in making changes and improvements for the better during the research process. The result of this research is the application of AI technology in promotional content by CV. Arbain Jaya Mandiri has proven to be an effective strategy in improving marketing strategies. This can provide insights for other micro businesses looking to optimize their digital strategies in small and medium-sized businesses for sustainable marketing strategies.